RETRACTED: Innovative technologies in teaching skating to children with intellectual disabilities - Voronova Elena; Koroleva Olga; Isakova Tatiana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001